Pengaruh Motivasi Dan Persepsi Mahasiswa Pada Psikologi Terhadap Prestasi Belajar Mata Kuliah Psikologi - Lela Nurlaila (Ta'lim: The Islamic Religious Educational Journal, 2024)
Academic achievement is a key indicator in evaluating the success of the learning process in higher education. Various psychological factors contribute to the attainment of academic achievement, particularly students’ motivation and their perceptions of the courses they take. This study aims to analyze the influence of motivation and students’ perceptions on the learning achievement in the Psychology course among students of the Guidance and Counseling Study Program at Nahdlatul Ulama University of Cirebon. This research employed a quantitative approach with multiple linear regression analysis. The research instruments consisted of a learning motivation questionnaire, a student perception questionnaire for the Psychology course, and documentation of final course grades. The sample included 78 students selected through purposive sampling. The findings indicate that motivation and students’ perceptions have a significant influence on academic achievement, with motivation serving as the most dominant contributing variable. These results emphasize the importance of internal student factors in determining the quality of learning outcomes.